Understanding the influences of social media in strength and conditioning practice: A prospective study of accredited strength and conditioning coaches - Morris, N. (Journal of Australian Strength and Conditioning, 2020)
Social Media (SM) is increasingly used by strength and conditioning coaches; however, there is little evidence about the how, what and why`s coaches use SM. To remedy this gap in the literature a qualitative study on the role of SM and how it influences the behaviours and actions of strength and conditioning coaches was conducted. The aims of this investigation were to examine the influences and behaviours of SM on strength and conditioning coaches. 107 strength and conditioning coaches responded to the survey with three omitted by the exclusion criteria. 97% of participants use SM, with Instagram (39.4%), Twitter (33.7%) the most popular platforms. Responses indicated that 91% believe the usage of SM is increasing in strength and conditioning coaches. 99% of participants understand the information shared on SM can be misleading, although 73% believe larger numbers of followers can influence the perception of quality of postings. Most coaches use SM to connect with other coaches (82%), to share or receive information (87%), and connect with athletes (45%), many also believe coaches use to criticise (43%) or debate (32%). 81% of respondents agreed or strongly agreed that SM can influence job or internship eligibility. If SM is used correctly it can be beneficial to the strength and conditioning coach. Coaches should act respectfully, (without criticising or denigrating others) and engage in collaboration, sharing of knowledge, and connection. It is important to remember the global reach of SM and always act professionally. These insights are intended to identify greater understanding around coaches` behaviours and influences of SM and establish practical applications for individual`s SM usage.